Earthquake: Earthquake waves, construction and working of seismograph, Earthquake zones of India, elastic rebound theory Preventive measures for structures constructed in Earthquake prone areas - Joshi, Prabha (New Panvel AIKTC, School of Engg. & Tech., 2016)
Learning eResources created by AIKTC faculty. An earthquake (also known as a quake, tremor or temblor) is the result of a sudden release of energy in the Earth$1 (Bs Crust that creates seismic waves. The seismicity or seismic activity of an area refers to the frequency, type and size of earthquakes experienced over a period of time. At the Earth's surface, earthquakes manifest themselves by shaking and sometimes displacement of the ground. When the epicentre of a large earthquake is located offshore, the seabed may be displaced sufficiently to cause a tsunami. Earthquakes can also trigger landslides, and occasionally volcanic activity.s
Keywords: Civil Engineering; Electronic Resources